KAJIAN MORFOMETRI BERDASARKAN TOPOGRAFI DAN POTENSI PERIKANAN WADUK SERMO - Bambang Triyatmo (Universitas Gadjah Mada, 2001)
The objectives of this studies was to know morphometric characteristics, primary productivity of water, and the fisheries potency of Sermo reservoir. Topography and fisheries potency were estimated based on a morphometrical study of Sermo reservoir after inundation. The study was conducted on the topographical maps with 1 : 12,500 scale and 10 m contour intervals. The primary productivity of Sermo reservoir after inundation was observed.The results showed that Sermo reservoir had an optimal level 136.6 m msl with a total water area 157 ha, water volume 25 millions m3, length of shore line 16,3 km and shore line development index 3,67. The primary productivity of water ranged from 2.2 to 178.7 mg C/m3/h. Potential area for fish culture using floating net cage was 1.5 ha with total production around 300 ton/year. The potency for endogenous and introduction fish production in the Sermo reservoir was approximately 5-10 ton/year.